Produccion y uso de biogas en instalaciones avicolas - Hidalgo Gato Esquere, G.=700 1 Silin, A.; Fraga, L.M.; Castellon, J.; Alfonso, O.
(Es, En)
Ilus., 6 ref.
Keywords: BIOGAS; FUENTE DE ENERGIA; PRODUCCION; EXCRETA; GALLINA PONEDORA; USOS; CUBA; REVISTA CIENCIAS TECNICAS AGROPECUARIAS